Validating Technology-Organization Environment (TOE) framework in web 2.0 adoption in supply chain management - Tarofder, Arun Kumar; Jawabri, Adnan; Haque, Ahasanul; Sherief, Sultan Rehman (Korean Institute of Industrial Engineers, 2019)
The second stage of Internet revolution has started with Web 2.0, which allows users to generate and develop the content without code. Web 2.0 not only change the way individual use internet but also tremendously transformed business activities. The primary aims of this study are (a) to validate the TOE framework in understanding Web 2.0 adoption in an organizational context, and (b) measuring the importance of each variable from the different industry perspective. This study developed a conceptual model based on the Technology-Organization-Environment (TOE) framework. A Webbased structured questionnaire was developed to collect primary data. With three months effort, this study managed to get 205 respondents from Malaysian manufacturing and service industry. Multiple regression and Dominance analysis were applied to understand the effect of the TOE framework on Web 2.0 adoption and predicting the importance of each factor form different industries perspective respectively. Multiple regression results confirmed that all the factors are important for Web 2.0 adoption, however, the technological characteristic is the most important determinant for Web 2.0 adoption. Moreover, dominance analysis showed very interesting results that relative advantage is not important for the service industry but top management support is the utmost importance. Similarly, results also indicated that top management support plays important role in Web 2.0 adoption for the fewer experience companies pertaining to internet usage. This study is one of the very few that provides insightful information regarding the effect of the TOE on Web 2.0 adoption in the supply chain management system. This study would be the guideline for the managers of both the manufacturing and service industry in order to implement the Web 2.0 in their supply chain system.